2020
DOI: 10.1007/s40121-020-00310-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Knowledge About the Impact of Augmented Renal Clearance on Antimicrobial Dosing in Critically Ill Patients: A Cross-Sectional Study

Abstract: Background: Broad-spectrum antibiotics are commonly prescribed in critically ill patients. While it is commonly believed that only patients with impaired renal function need dose adjustment, augmented renal clearance (ARC) is a phenomenon that warrants dose adjustment as well. In critically ill patients ARC is often undetectable because it is associated with a normal or decreased serum creatinine concentration (SCr). This study's objective was to assess pharmacists' knowledge about ARC identification, risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…30,31 This may lead to augmented renal clearance (ARC) of drugs from the circulation, thereby lowering the circulating concentration more rapidly than would occur in noncritically ill patients. 32,33 Human studies 17 have demonstrated ARC in approximately half of critically ill patients requiring antimicrobial therapy. Those patients with ARC also showed a greater rate of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 This may lead to augmented renal clearance (ARC) of drugs from the circulation, thereby lowering the circulating concentration more rapidly than would occur in noncritically ill patients. 32,33 Human studies 17 have demonstrated ARC in approximately half of critically ill patients requiring antimicrobial therapy. Those patients with ARC also showed a greater rate of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…This was a cross-sectional study. Data were collected as previously described in Almulhim, Al-Dahneen & Alsowaida (2020) . In short, an electronic link was sent to three scientific organizations: Saudi Pharmaceutical Society (SPS), Kuwait Pharmaceutical Association (KuPhA), and Oman Pharmaceutical Society (OmPhS).…”
Section: Methodsmentioning
confidence: 99%